Analisis Efektivitas Kelembagaan Pengelolaan Hutan Bersama Masyarakat (PHBM) di KPH Bandung Utara Jawa Barat - Bahruzin Bahruzin; Aceng Hidayat; Eka Intan Kumala Putri (Journal of Agriculture, Resource and Environmental Economics, 2014)
Community-based forest management (CBFM) was aimed to achieve the sustainability of forest functions and to omptimize its benefits. CBFM around the Forest Lap Area in North Bandung is a joint forest management between Perum Perhutani and forest villagers. The purposes of this study were; (1) to analyse the processes and stakeholders of CBFM, (2) to analyse the institution effectiveness of CBFM, (3) to analyse the result of the CBFM implementation The approach of this research was the stakeholder analysis and IPA (importance of Performance Analysis). The result of stakeholder mapping showed that Perum Perhutani and LMDH had the role in the implementation of CBFM system. The results of the economic impact of CBFM calculations indicated that the system could increase the income of MDH. This was indicated by the change in the average income of farmers by 63%. The result of IPA could be seen from the mapping of availability level of forest resources and forest resource need for the community included in B quadran in which it had a high level of availability and interest.